PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hera, Maria Dominika Edo; Pinem, Dahlia Br (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
The purpose of this study was to examine the effect of liquidity and capital structure on firm value with profitability as intervening variable. The population in this study is the consumer goods sector companies listed in the Indonesia Stock Exchange from 2013-2016. Sampling technique using purposive sampling method, with samples produced as many as 20 companies from 37 companies of consumer goods sector. This hypothesis testing uses Path Analysis with E-Views 9.0 and a significance level of 5%. Test results of the testing showed that (1) liquidity has a significant effect on profitability with significance level 0,0192 < 0,05. (2) capital structure has a significant effect on profitability with a significance level of 0.0003 < 0,05. (3) liquidity has no effect on firm value because of the significance level of 0.09982> 0.05. (4) capital structure has a significant effect on firm value with significance level 0,0000 < 0,05. (5) profitability has a significant effect on firm value with significance level of 0.0001 < 0,05. (6) liquidity and capital structure has no effect on firm value through profitability because the indirect influence of both variables is smaller than direct influence.